Effects of Exercise Training on the Autonomic Nervous System with a Focus on Anti-Inflammatory and Antioxidants Effects - Matei Daniela; Luca Catalina; Onu Ilie; Matei Paula; Iordan Daniel-Andrei; Buculei Ioana (MDPI AG, 2022)
Studies show that the autonomic nervous system (ANS) has an important impact on health in general. In response to environmental demands, homeostatic processes are often compromised, therefore determining an increase in the sympathetic nervous system (SNS)'s functions and a decrease in the parasympathetic nervous system (PNS)'s functions. In modern societies, chronic stress associated with an unhealthy lifestyle contributes to ANS dysfunction. In this review, we provide a brief introduction to the ANS network, its connections to the HPA axis and its stress responses and give an overview of the critical implications of ANS in health and disease-focused specifically on the immune system, cardiovascular, oxidative stress and metabolic dysregulation. The hypothalamic-pituitary-adrenal axis (HPA), the SNS and more recently the PNS have been identified as regulating the immune system. The HPA axis and PNS have anti-inflammatory effects and the SNS has been shown to have both pro- and anti-inflammatory effects. The positive impact of physical exercise (PE) is well known and has been studied by many researchers, but its negative impact has been less studied. Depending on the type, duration and individual characteristics of the person doing the exercise (age, gender, disease status, etc.), PE can be considered a physiological stressor. The negative impact of PE seems to be connected with the oxidative stress induced by effort.